FAKTOR-FAKTOR YANG MEMPENGARUHI TAKSIRAN BERAT JANIN PADA IBU HAMIL TRIMESTER III DI BPM MITRA ANANDA PALEMBANG TAHUN 2019 - Rinda Lamdayani; Varadita Olivia (Jurnal Kesehatan Abdurrahman, 2019)
Fetus weight estimation is considered important during pregnancy because intra-uterine fetal growth is not constant and is associated with an increased risk of complications during labor in the mother and baby, such as low birth weight or excessive birth weight. This study aimed to determine the factors that affect the estimated weight of the fetus in third trimester of pregnant women. This study used the analytical survey method with Cross Sectional approach at PMP MitraAnanda Palembang. The data collected by using secondary data and the number of samples taken was as many as 134 respondents. Bivariate results analyzed using Chi-Square. The result showed that there was no significant correlation between hemoglobin level (p value 0.370) and maternal age (p value 0.164) with fetus weight estimation. However, there was a significant correlation between the size of upper arm circumference (p value 0,000) and the increase in body weight (p value 0,000) with fetus weight estimation. There was no significant correlation between hemoglobin levels and the age of the mother with fetus weight estimation in the third trimester and there was a significant correlation between the size of upper arm circumference and the increase in body weight with fetus weight estimation in the third trimester of pregnancy. Taksiran berat janin dianggap penting pada masa kehamilan karena pertumbuhan janin intra uterin berlangsung tidak konstan dan berhubungan dengan meningkatnya risiko terjadinya komplikasi selama persalinan pada ibu dan bayi seperti berat lahir rendah atau berat lahir berlebih.Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi taksiran berat janin pada ibu hamil trimester III. Penelitian ini menggunakan metode Survei Analitik dengan pendekakatan Cross Sectional di BPM Mitra Ananda Palembang dengan pengambilan data mengunakan data sekunder dan jumlah sampel yang diambil sebanyak 134 responden. Hasil bivariat menggunakan Chi-Square: tidak ada hubungan kadar hemoglobin (p value 0,370) dan umur ibu (p value 0,164) dengan taksiran berat janin, serta ada hubungan ukuran LILA (p value 0,000) dan kenaikkan berat badan (p value 0,000) dengan taksiran berat janin. Tidak terdapat hubungan antara kadar Hb dan umur ibu dengan taksiran berat janin pada ibu trimester III serta terdapat hubungan antara ukuran LILA dan kenaikkan berat badan dengan taksiran berat janin pada ibu hamil trimester III.